2020
DOI: 10.1016/s2215-0366(20)30128-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for adults with dissociative seizures (CODES): a pragmatic, multicentre, randomised controlled trial

Abstract: Background Dissociative seizures are paroxysmal events resembling epilepsy or syncope with characteristic features that allow them to be distinguished from other medical conditions. We aimed to compare the effectiveness of cognitive behavioural therapy (CBT) plus standardised medical care with standardised medical care alone for the reduction of dissociative seizure frequency. MethodsIn this pragmatic, parallel-arm, multicentre randomised controlled trial, we initially recruited participants at 27 neurology or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
166
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 204 publications
(190 citation statements)
references
References 34 publications
1
166
1
Order By: Relevance
“…We collected a wide range of clinical and demographic variables. Some of these measures were collected at consent to the screening phase of the overall study (Goldstein et al, 2019) and some were collected immediately pre-randomisation. We also recorded the Index of Multiple Deprivation (IMD) which gives a postcode-based measure of deprivation by locality, using the databases that were applicable when data collection commenced (Ministeries of Housing Communities and Local Government, 2010;Scottish Government, 2012;Welsh Government, 2011).…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected a wide range of clinical and demographic variables. Some of these measures were collected at consent to the screening phase of the overall study (Goldstein et al, 2019) and some were collected immediately pre-randomisation. We also recorded the Index of Multiple Deprivation (IMD) which gives a postcode-based measure of deprivation by locality, using the databases that were applicable when data collection commenced (Ministeries of Housing Communities and Local Government, 2010;Scottish Government, 2012;Welsh Government, 2011).…”
Section: Demographicsmentioning
confidence: 99%
“…Patients developing DS over the age of 55 were more likely to be male, less likely to report previous sexual abuse, but more likely to report health-related traumatic experiences in one particular study (Duncan et al, 2006); in additon, there was a trend towards better mental health in the later onset subgroup. We have recently demonstrated that earlier age at DS onset is largely seen in women while men appear likely to develop DS at any age (Goldstein et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The success rate of ReACT is higher than studies using CBT for PNES in adults. 20,21,23,24 However, it is unclear if this is due to a difference in PNES between pediatric and adult populations or due to the treatment targets of the CBT treatments whereas adult PNES CBT treatments target fear avoidance 21,22 and work to reattribute patients' symptoms to psychosocial issues, 20,23,34 while ReACT aims to decrease catastrophic symptom expectations and directly retrain physical PNES symptoms in order to increase patients' control over their symptoms. 35 Second, it is noteworthy that significant reductions in PNES were demonstrated after ReACT, while anxiety and depression were not significantly changed.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In the largest RCT assessing CBT for PNES in adults by targeting fear avoidance, there was no difference in PNES between CBT with standard medical care and standard medical care alone at 12 months after treatment. 24 These negative results suggest mood is not the most effective PNES treatment target and support the investigation of novel treatment targets.…”
Section: Introductionmentioning
confidence: 99%